Teaching Social Identity - Samuel M Nelson (Middle Grades Review, 2021)
Early adolescence is a time for students to move beyond interests-based definitions of themselves - things like, "I am a soccer player." Middle school students must begin to recognize and understand how a mosaic of social identifiers constitutes an individual’s social identity. Identifiers are characteristics like race, ethnicity, sexuality, gender identity, gender performance, physical & sensory ability, religion, and many more. This essay explains why making social identity a central curricular pillar is crucial, how to do so in an engaging, meaningful way, and what it can look like once students have the understanding of social identity to use as a tool for constructing or unpacking class content.
Keywords: Social Identity; Personalized Learning; Social Identifiers; Intersectionality